Persepsi tentang nutrition claims, perilaku makan, dan body image antara mahasiswi kesehatan dan non-kesehatan - Ahmed Fahmy Arif Tsani; Ananda Eka Astirani; Restu Amalia Hermanto; Lisa Indraswari; Okky Lupitasari; Cita Eri Ayuningtyas (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: Food Marketing Institute survey results showed that 57% of consumers choose products with whole grain claims, 54% high fiber, and 53% low fat. In Indonesia, there is increasing public demand for products of low fat and high fiber. A person with a high level of knowledge, especially in those who have knowledge of health, should have a better understanding. However, it becomes difficult in transition adolescence to early adulthood period. Concern about body image to be the reason which more students choose foods that are believed to maintain the appearance remains interesting, such as on products with nutrition claims.Objective: To determine differences in perception of nutrition claims, food behaviors, and body images on health and non-health students.Method: This type of research is an observational study with cross-sectional design with two groups. The respondents were Gadjah Mada University students aged 19-24 years. Subject selection is based on consecutive sampling technique.Results: Perceptions of nutrition claims between health and non-health students differ significantly (p=0.000). In both groups, the food behavior which includes the consumption of fat (p=0.803) and fiber (p=0.926) did not differ, whether from food or natural products. There is no significantly difference in body image between the two groups (p=0.463).Conclusion: Between health and non-health students have different perceptions of nutrition claims, but there is no difference in food behaviours and body image between the two groups.